The differences of nature experiences between urban and rural children - Nor Diyana Mustapa,; Nor Zarifah Maliki,; Nor Fadzila Aziz,; Aswati Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aims to investigate the differences between urban and rural children in experiencing nature through direct experiences and indirect experiences, as well as non- nature experiences. Questionnaires were distributed to 760 children from 20 schools located in urban and rural areas in Kedah and Penang, Malaysia. The data were analysed using mean score, standard deviation and one-way analysis of variance. The results confirmed that direct experiences with nature among children in both urban and rural areas have declined and children obtain nature experiences mostly through indirect experiences. The results also showed that there were differences between urban and rural children in experiencing nature. Rural children have slightly more direct experiences with nature as compared to children in urban areas, but further analysis showed that the differences of direct experiences between children in Urban Kedah and Rural Kedah were the one that significantly differ with each other. As for indirect experiences, urban children have more indirect experiences with nature as compared to rural children. Meanwhile, for non-nature experiences, there was no difference between urban and rural children. Overall, this study suggests that urban and rural location do influence the frequency of children’s experiences with nature particularly the frequency of direct experiences with nature. However, having nearby nature within children’s places and spaces is rather more important in making a significant difference on how frequent children have direct experiences with nature. This study further highlights the importance to reconnect both urban and rural children with nature within their daily places and spaces such as home yard, neighbourhood areas, playground, and schools. The directions of future research are also discussed.